The Story of Dhon Cholecha: A Structural Analysis - Narendra Raj Subedi (Interdisciplinary Journal of Management and Social Sciences, 2022)
Folktales are part of folk literature, which is more widely referred to as folklore. Every community has its own folklore and it has been widely practiced since the time immemorium. It is the oral art of the common people representing the contributions of many anonymous creators. Folktales are regarded as the simplest form of narratives these tales have their own structures. Tales of these types from various cultures have also been analyzed in terms of their structures. In the present study Vladimir Propp can be considered for the structural analysis of a Nepali tale. After the publication of his book Morphology of the folktale the folklorists got a new approach to reveal the tales from its structures. So, this research article tries to explore the structures of a Nepali folktale using a tale to explore its own structures. To make a whole it advocates an investigation of the relationship between forms and suggests a structural analysis. In this context a tale from Tales of Kathmandu "The story of Dhon Cholecha" has been analyzed to meet the aforementioned objective. Since this tale has its narrative structure where we find two different moves and can be diagnosed as the first move and the second move and they run in a quite contrastive way, so from this type of contradiction the tale can be analyzed in terms of contrastive structure analysis from the narrative of "Dhon Cholecha" which contributes for the ‘social purpose’ of story telling as well.